IDENTITY THEMES IN THE WORKS OF SERBIAN ARTISTS IN KOSOVO AND METOHIJA UNTIL THE 1990 (Heritage, 2021)
The paper discusses the issue of identity themes in the work of contemporary Serbian artists in Kosovo and Metohija, until the 1990s.Among Serbian artists were those who nurtured themes related to the Serbian cultural identity of the 1970s and 1980s. The painter VladaRadović expressed this through the works of “The Patriarchate of Peć”, “The Forest of Dečani with a view of the VisokiDečan Monastery and “The Holy Virgin Ljeviška”. After him, Sava Rakočević, in his creative beginnings, also sought and found inspiration in the Kosovo pledge and in Kosovo as a space woven into Serbian cultural identity. His painting “Monument to the Kosovo Heroes” is a representative example. TrajkoStojanovcicKosovac also drew inspiration from Kosovo-pledge inspiration in even more difficult times. His aquatint and graphics cycle is dedicated to Dečani - the treasury of Serbian spirituality and culture.In Trajko Kosovac's studio, Zoran Furunovichad been working on copying murals before enrolling basic studies, where we recognize his interest in topics related to Serbian cultural identity.Initiated by the entire situation in the entire Kosmet area, where everything is directed against the people of Serbian nationality, the painter Petar Đuza with a direct response and through the paint "Heroics of Myth Grows Into Tragic Reality" provides the observer with an overview of unpleasant events. In the 1970s and 1980s, Svetomir Arsić Basara, as the leading Serbian sculptor in the Province, began to show through sculpture the impossibility of reconciling with the threat to Serbian national and cultural identity.
Keywords: Kosovo and Metohija, identity, fine arts, Vlada Radović, Sava Rakočević, Trajko Stojanović Kosovac, Svetomir Arsić Basara, Petar Đuza, Zoran Furunović.